Development of Edugames on Pancasila Material to Improve Learning Outcomes of Grade IV Students in Elementary Schools - Irfan Dahnial (Institut Agama Islam Negeri Palopo, 2024)
This research and development project utilizes the 4-D model, comprising four stages: definition, design, development, and dissemination. The research was conducted at MIN 6 Langkat from September to November during the 2024/2025 academic year. The participants included 20 fourth-grade students, 11 of whom were female and nine were male. The edugame focused on Pancasila material, which was the subject of this study. Data collection involved observation, interviews, questionnaires, and testing. The gathered data were analyzed using two methods: (1) an analysis of the edugame's feasibility and (2) an analysis of its effectiveness. The validation from language experts yielded a score of 88.65%, which falls under the feasible category. In comparison, material experts rated it at 90.10%, classifying it as very feasible, and media experts provided a score of 96.75%, marking it as very feasible. The students’ pretest average in the trial was 35.07%, and the post-test score increased to 64.93%. Based on the validation and trial results, it can be concluded that the edugame on Pancasila content for grade IV students at MIN 6 Langkat is both feasible and effective.